1976
DOI: 10.4992/psycholres1954.18.174
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and Qualitative Analysis of Experience in Acquisition of a Miniature Artificial Language

Abstract: so examine the quantity and quality of experience required to acquire a phrase structure grammar, the numbers of exemplars and reference conditions were controlled, using a miniature artificial language. The results showed that (a) under Semantic Referent Conditions a constant amount of experience was necessary for syntax acquisition; (b) semantic referents facilitated the overall acquisition of the syntax; but (c) even under Non-Semantic Referent Conditions some Ss could acquire the syntax. These results were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 30 publications
(37 reference statements)
1
10
0
Order By: Relevance
“…One account of the present results is based on the observation that the variations in synthetic speech that must be learned are lawful and rule-governed much as the variations in artificial-language materials are (e.g., Nagata, 1976;Palermo & Parish, 1971). Under these conditions, learning of a repeated training set appears to produce the same level of generalization as does training with novel stimuli as long as the number of presentations is the same for the two training procedures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One account of the present results is based on the observation that the variations in synthetic speech that must be learned are lawful and rule-governed much as the variations in artificial-language materials are (e.g., Nagata, 1976;Palermo & Parish, 1971). Under these conditions, learning of a repeated training set appears to produce the same level of generalization as does training with novel stimuli as long as the number of presentations is the same for the two training procedures.…”
Section: Resultsmentioning
confidence: 99%
“…Based on earlier research in pattern learning (e.g., Dukes & Bevan, 1967;Posner & Keele, 1968), subjects trained on novel exemplars should show more improvement than do those trained with repeated exemplars, because the novel training set provides a broader sample of the acoustic-phonetic variability in Votrax speech than is provided by the repeated training set. However, from artificial-language learning studies (e.g., Nagata, 1976;Palermo & Parish, 1971), we predict that if the repeated training set sufficiently characterizes the underlying acoustic-phonetic structure of the synthetic speech, there should be no performance difference between subjects receiving repeated training stimuli and those presented with novel training stimuli (as long as both sets of subjects receive an equal number of exemplars).…”
Section: Methodsmentioning
confidence: 99%
“…The presence of semantic information has been proposed to affect the learning (Moeser and Bregman, 1972 ; Amato and MacDonald, 2010 ; Poletiek and Lai, 2012 ; Poletiek and Monaghan, unpublished manuscript) and processing (Howard and Ballas, 1980 ; Spivey et al, 2002 ) of complex structures in natural language. Making exemplars meaningful by adding a reference field (e.g., visual illustrations of scenes they refer to) has often been shown to enhance the learning of phrase structure grammars, which specify the relations between classes of elements (Nagata, 1976 ; Mori and Moeser, 1983 ; Meier and Bower, 1986 ; Valian and Coulson, 1988 ; Amato and MacDonald, 2010 ; see also Van den Bos et al, 2012 ). Moreover, two such studies have shown that the presence of a visual reference field can compensate negative effects of complexity of the grammar (Moeser and Bregman, 1972 ; Nagata, 1977 ).…”
Section: Introductionmentioning
confidence: 99%
“…These results clearly indicate that language acquisition may be mediated by nonlinguistic semantic aspects of a context. Nagata (1976), on the other hand, showed not only that semantic reference facilitated overall acquisition of the syn-tax, but that syntax acquisition also occurred for some subjects who were not given semantic reference. Since the complexity of syntax utilized by Moeser and Bregman (1972) and Nagata (1976) differed considerably, Nagata (1976) suggested that as the complexity of syntax increases the presence of semantic reference becomes necessary.…”
Section: The Interaction Between Syntactic Complexity and Semantic Re...mentioning
confidence: 93%
“…Nagata (1976), on the other hand, showed not only that semantic reference facilitated overall acquisition of the syn-tax, but that syntax acquisition also occurred for some subjects who were not given semantic reference. Since the complexity of syntax utilized by Moeser and Bregman (1972) and Nagata (1976) differed considerably, Nagata (1976) suggested that as the complexity of syntax increases the presence of semantic reference becomes necessary. This implies that whether semantic reference is necessary or not for syntax acquisition depends on a level of syntactic complexity.…”
Section: The Interaction Between Syntactic Complexity and Semantic Re...mentioning
confidence: 93%